Optimizing artificial insemination in goats: semen deposition site and vaginal mucus characteristics as predictive biomarkers - Kang, Ting-Chieh; Tseng, Kai-Fei; Lin, Hsin-Hung; Chen, Tsai-Tzu; Lai, I-Ling; Shen, Perng-Chih (Frontiers in Veterinary Science, 2025)
Artificial insemination (AI) is a critical tool for genetic improvement and fertility management in goats. This study examined the effects of semen deposition site (uterine body, cervix, vagina) and vaginal mucus type (cloudy, turbid, clear) on pregnancy rate, kidding rate, and average litter size in 300 CIDR-synchronized Alpine does in southern Taiwan. Semen deposited in the uterine body combined with cloudy mucus yielded the highest pregnancy rate (55.9%), while vaginal deposition with clear mucus resulted in the lowest (30.7%). Two-way ANOVA showed significant main effects and interactions for pregnancy rate and average litter size (p < 0.05), but no significant effect on kidding rate. Pregnant does exhibited lower vaginal mucus electrical conductivity, higher pH, and elevated temperature compared to non-pregnant does, suggesting these parameters as potential biomarkers for estrus detection. Findings highlight the importance of precise semen placement and optimal mucus condition for improving AI protocols in goats.